O estreito fio da navalha: participação e transformismo na relação do Movimento dos Conselhos Populares (MCP) com a Gestão de Luizianne Lins em Fortaleza (2005-2009) - Costa Júnior, Pedro Wilson Oliveira da (2010)
This dissertation investigates the Movement of Popular Councils (MCP), urban social movement that since 2004, serves the city of Fortaleza. The focus of this movement is the relationship with local government, ruled by Luizianne Lins, Workers Party (PT). This process is collated redesigns with it, in course, Brazil, of the left and the social movements, decurrent of the ideological transformations suffered by the PT in recent years and accented by the consolidation of a new hegemony politics led for Lula and anchored in an ample consensus between social classes.